Free radicals and antioxidant system - Guija-Guerra, Henry (2023)
Free radicals are compounds characterized by having an unpaired electron in their outer orbit, a condition that makes them highly reactive, i.e., they interact through diffusion-controlled reactions with proteins, lipids and nucleic acids.They have also been referred to as reactive oxygen species (ROS), reactive nitrogen species (RNS) or reactive sulfur species(RSS). In the human organism, they are mainly produced in the mitochondrial electron transport chain, where respiratorycomplexes I and III specifically participate and reduce oxygen by converting it into superoxide anion. Likewise, they canbe formed through a wide variety of enzymatic and non-enzymatic reactions involving substances that are synthesized by cells or are ingested with food and some medicines. Human beings have an antioxidant system which is both enzymaticand non-enzymatic in nature and whose function is to protect the organism from the harmful action of free radicals. Thissystem includes enzymes—such as catalase, superoxide dismutase, thioredoxin, etc.—and non-enzymatic compounds—such as glutathione, ferritin, myoglobin, etc. However, they are not efficient enough to protect it, so it is necessary to eat foods that contain substances with antioxidant properties whose protective action will depend on their chemical reactivity and their concentration. These antioxidant compounds are mainly found in fruits and vegetables, where polyphenols, flavonoids, carotenoids, vitamin C, vitamin E, etc. have been identified. A significant amount of evidence suggests that the intake of antioxidant substances protects the body from the damaging effect of free radicals, but when the oxidative action prevails over the antioxidant action, it can lead to oxidative stress, a condition that is closely linked to a wide variety of chronic non-communicable diseases including cancer, diabetes mellitus, obesity, psoriasis, atherosclerosis,among others. All this seems to indicate that the term “cellular redox steady state” more appropriately describes the constant adaptation to a situation of rapid chemical turnover and suggests that the substances involved in this process be designated as “biologically reactive species” due to the existence of harmful compounds such as hydrogen peroxide, peroxynitrite, etc., which are not—strictly speaking—free radicals but have toxic effects on cells.